2013
DOI: 10.1111/ors.12023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of septa frequency in the maxillary sinuses with edentulous and dentulous areas through computed tomography

Abstract: Objective: To analyse the number of septa in the maxillary sinuses using computed tomography (CT) in correlation with gender, age and the presence of teeth in the region. Materials and methods: The sample consisted of 300 CT scans obtained from a private radiology clinic between 2009 and 2011. The CT scans included in the study should have the appropriate image of the maxillary sinus and contain information regarding age, gender and the date of the examinations. Patients with a history of pathologies in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
3
1
1
Order By: Relevance
“…1,7,14 The reported prevalence of septa in studies using the 3D imaging techniques has been variable from 25% to 70%. 1,[5][6][7][8]10,14,[20][21][22][23][24] In our study, the prevalence of septa was 44.8% in all patients, which is in accord with the results of Neugebauer et al 1 Panoramic radiography is the most commonly used 2-dimensional (2D) imaging modality. Owing to several limitations, it is not used before implant placement alone.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1,7,14 The reported prevalence of septa in studies using the 3D imaging techniques has been variable from 25% to 70%. 1,[5][6][7][8]10,14,[20][21][22][23][24] In our study, the prevalence of septa was 44.8% in all patients, which is in accord with the results of Neugebauer et al 1 Panoramic radiography is the most commonly used 2-dimensional (2D) imaging modality. Owing to several limitations, it is not used before implant placement alone.…”
Section: Discussionsupporting
confidence: 94%
“…Most studies that used CT reported a relatively lower prevalence for septa than our value, [6][7][8]10,16,20,28 except for Maestre-Ferrín et al 5 who reported 70% incidence. CT as a 3D technique can reveal the anatomical details of the maxillary sinus.…”
Section: Discussioncontrasting
confidence: 51%
“…The present study found no relationship between dental status (dentate, partially edentulous, edentulous) and the prevalence of septa (63.8% of dentate, 22.1% of partially edentulous, and 14.1% of edentulous). This finding is consistent with Shen et al [ 22 ] who observed no correlation between septa prevalence and the absence of maxillary first or second molars, consistent with recent studies [ 2 , 14 , 21 , 24 , 38 , 39 ]. The present study contradicts other studies [ 35 , 40 , 41 ] which showed edentulous ridges have more septa than dentate ridges, as concluded by Krennmair et al and Kim et al, who proposed the hypothesis that atrophic edentulous maxilla considers secondary septa [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…This nding is consistent with Shen et al [22] who observed no correlation between septa prevalence and the absence of maxillary rst or second molars, consistent with recent studies [2,18,21,[42][43][44]. The present study contradicts other studies [38, 45,46] The thickness of the membrane at the septa origin is almost twice as thick as it is from the septa origin [53].…”
Section: 1│sinus Septa Variations and Morphologysupporting
confidence: 92%